(untitled) (The Research of Medical Science Review, 2024)
To determine the effect of the azithromycin on QTc interval in terms of absence or presence of prolongation in children admitted in Children’s Hospital Lahore, Pakistan, The study utilized observational prospective study to test the effect of Azithromycin on QTc interval in children, The study was conducted at the general medical unit of the Children’s Hospital Lahore within six months after approval from hospital ethical committee, 102 patients visiting the Children hospital Lahore, fulfilling the inclusion criteria, were selected using non-probability consecutive sampling technique. A written informed consent was taken from parents (father or mother) followed by child assent. Detailed history was taken including age, gender, weight, diagnosis, and any underlying chronic ailment. A baseline ECG and serum electrolytes were taken before starting azithromycin. Then, a serial ECG was taken on each day for a total of five days and QTc interval was calculated. All the collected data were entered and analyzed using SPSS (v. 24), The mean age of patients was 6.88 ± 3.44 years with male to female ratio of 1:1.22. The mean value of QTc interval at baseline was 403.90 ± 12.18 ms, after two days it was 402.47 ± 11.87 ms, after three days it was 402.94 ± 12.02 ms, after four days it was 403.80 ± 12.12 ms, and after five days it was 405.90 ± 18.77 ms. In current study, the QTc prolongation was observed in six (5.9%) patients, It was concluded that there was no statistically significant effect of azithromycin on the ventricular repolarization parameters (QTc) on electrocardiogram (ECG) in pediatric patients treated with azithromycin.